Blog : eu te lendo e eu te escrevendo - Silveira, Mariane Rocha (2010)
The present study has as goal to discuss the relations between the new technologies available in the post-modern reading and writing society, the blogs, and the supposed new subjects, gifted with cognitive abilities and capacities, that challenge the still monologic way of teaching in the educational institutions. For this, a bibliographic research and, later, a field research were made on the molds of the case study. The bibliographic research redeemed the emergence and the historical path of the school making reference specifically on the reading and writing practices with Literature and the new relations with the plural reading, emergent from the XXI century. It is also presented some studies from theorists that have named differently the people that have been born in the digital era, like, Veen and Wrakking (2009) and the Homo Zappiens, Santaella (2004) and the immersive reader and Xavier (2007), the hyperreader 2.0. Yet, it is mentioned the reading and writing digital support on the internet, the virtual diaries known as blogs, its specifications, the genders, or the types of blogs and its changes into other writing possibilities, as in the microbloggings. After that, on the field research, the blog was presented to the subjects of the research, students from the 8th grade, in practices involving the reading and writing skills, in the hypothesis that if kids are working in digital support, where the multimedia reigns, it would happen a representative qualitative change in the reading and writing formation of the own subjects of this research